Magnesium modulates the stress responses of oral streptococci to environmental and antibiotic challenges by altering cell envelope and nutrient transport pathways - Mishra, Surabhi (Frontiers in Microbiology, 2026)
BackgroundMagnesium (Mg2+) is one of the most abundant metals in human teeth, second only to calcium. Demineralization of the tooth, caused by sugar intake or acid reflux, releases Mg2+ into the saliva. Mg2+ is also recommended as a dietary supplement for the prevention and treatment of chronic diseases. Oral streptococci, therefore, must regulate Mg2+ homeostasis to adapt to fluctuating levels of saliva in the human oral cavity.Materials and methodsWe determined the toxic concentration of MgCl2 for Streptococcus spp. and used a sub-toxic dose to assess its effect on osmotic and cation-excess stress tolerance. Growth assays, ICP-MS, proteomic analysis, and lipidomic analysis were performed on wild-type and mutant strains lacking a putative Mg2+ efflux pump homolog.ResultsMg2+ supplementation enhanced tolerance to osmotic and cation-excess stress in both caries-associated and commensal streptococci. Homologs of the magnesium protection factor A (MpfA) were found across Streptococcus groups. Mutants lacking mpfA homologs (smu_1693 in S. mutans, and ssa1761 in S. sanguinis) showed MgCl2 sensitivity. Despite unchanged intracellular Mg2+ levels in Δsmu_1693, the mutant exhibited stress tolerance, consistent with the disruption of magnesium efflux pumps. Proteomic and lipidomic analyses revealed altered levels of amino acid transporters, cell envelope proteins, and an increase in long-chain unsaturated fatty acids. Furthermore, modulating intracellular Mg2+ concentration, either by MgCl2 supplementation or by eliminating HlyX, impacted the efficacy of multiple cell wall-targeting antibiotics.ConclusionThis study highlights the role of Mg2+ in enhancing stress tolerance and modulating antibiotic sensitivity in streptococci, using S. mutans as a model.